Should mothers work? How perceptions of the social norm affect individual attitudes toward work in the U.S. - Patricia Cortés; Gizem Koşar; Jessica Pan; Basit Zafar (Federal Reserve Bank of New York, 2022)
We study how peer beliefs shape individual attitudes toward maternal labor supply using realistic hypothetical scenarios that elicit recommendations on the labor supply choices of a mother with a young child and an information treatment embedded within representative surveys. Across the scenarios, we find that individuals systematically overestimate the extent of gender conservativeness among the people around them. Exposure to information on peer beliefs leads to a shift in recommendations, driven largely by information-based belief updating. The information treatment also increases (intended and actual) donations to a nonprofit organization advocating for women in the workplace.
Keywords: D84; J22; C83; 330; expectations; social norms; information treatmen